2009
DOI: 10.1016/j.jns.2009.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Speeding stroke recovery?

Abstract: Introduction: The use of drugs to enhance recovery ('rehabilitation pharmacology') has been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Thus, the agents used for PA seem relatively safe. None of our patients had piracetam or amphetamines, about the safety of which there is doubt [16,17,18]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the agents used for PA seem relatively safe. None of our patients had piracetam or amphetamines, about the safety of which there is doubt [16,17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to meta-analyses across several studies, there were some concerns about safety of some agents (i.e. piracetam [16] and amphetamines [17,18]). More research is necessary [16].…”
Section: Introductionmentioning
confidence: 99%
“…This list was based on reviews covering several drugs [11,13,23] and on reported studies about specific agents: levodopa [4,5,15], dopamine agonists [6], selective serotonin reuptake inhibitors (SSRI) [24,25], serotonin-noradrenaline reuptake inhibitors (SNRI) [26], acetylcholinesterase inhibitors [7,8], modafinil [27], methylphenidate [10,28], and memantine [29]. D -Amphetamines [20,21] were not considered because of their unavailability.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the clinical evidence regarding benefits of this treatment approach is still considered weak [11] and future research is recommended [12,13] for the following reasons: (1) the beneficial findings of some studies [4,5,6,7,8,9,10] were not confirmed by others [14,15,16,17,18,19], (2) several studies were limited by small patient populations and narrow inclusion criteria, and (3) there were some concerns regarding safety of some agents (i.e. piracetam [13] and amphetamines [20,21]). It is not well known how often agents potentially enhancing post-stroke recovery have been used in practice outside clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Although amphetamine was associated with a trend to improved motor function after IS in a systematic review, there was a non-significant increase in death, raising doubts over its safety. 82 Other potential agents including norepinephrine (noradrenaline), epinephrine (adrenaline) and dopamine have no significant evidence base. 79 …”
Section: Nitric Oxide Donorsmentioning
confidence: 99%